Events Dedicated to the 750-Year Anniversary of the Golden Horde - Sayfetdinova E.G. (Золотоордынское обозрение)
The year 2019 is progressing under the auspices of the celebration of the 750th anniversary of the Talas kurultai, an event which served as the starting point in shaping the independence of the Golden Horde and other Chingissid states. The 1269 kurultai is conventionally seen as the date of peace between the Chingissids and the definition of the boundaries of their domains. It is also widely accepted that the 1269 kurultai completed in legal terms the process of disintegration of the Mongol empire. The decisions taken at the kurultai not only legally confirmed the dissolution of the Mongol empire, but also allowed the Jochid ulus to become a truly sovereign state – the Golden Horde. A number of events held both in the Russian Federation and in other countries are timed to this event. The anniversary events aroused the interest of not only specialists of the Golden Horde theme, but also attracted wide public interest.